Collection of the Abstracts of the 2019Sp PMD: Translational Myology and Mobility Medicine - Ugo Carraro (PAGEPress Publications, 2019)
A half-century tradition of studies of skeletal muscles, that started with a research on fever, specifically if and how skeletal muscle contributes to it by burning bacterial toxin, are continuing under the auspices of the Interdepartmental Research Centre of Myology (CIR-Myo), Department of Biomedical Sciences, University of Padova, Italy and the A&C M-C Foundation for Translational Myology, Padova, Italy. This year the 2019SpringPaduaMuscleDays: Translational Myology and Mobility Medicine, an International Conferences organized in Euganei Hills and Padova (Italy), was held March 28-30, 2019. The abstracts of 2019SpPMD present excellent examples of translational research. Their contents are at the high level needed to be approved by Ethical Committees, International Granting Agencies and Editors of international journals. This will be true in the future thanks to the high quality of the researchers who are eager to present their results during the PaduaMuscleDays.